Peanut protein structure, polyphenol content and immune response to peanut proteins in vivo are modulated by laccase. Issue 5 (3rd May 2016) - Mihajlovic, L.; Radosavljevic, J.; Nordlund, E.; Krstic, M.; Bohn, T.; Smit, J.; Buchert, J.; Cirkovic Velickovic, T.
Abstract : Laccase cross-linking of peanut protein causes changes in the protein structure, phenolic composition and immunological properties of the treated peanut protein. Abstract : Food texture can be improved by enzyme-mediated covalent cross-linking of different food components, such as proteins and carbohydrates. Cross-linking changes the biological and immunological properties of proteins and may change the sensitizing potential of food allergens. In this study we applied a microbial polyphenol oxidase, laccase, to cross-link peanut proteins. The size and morphology of the obtained cross-linked proteins were analyzed by electrophoresis and electron microscopy. Structural changes in proteins were analyzed by CD spectroscopy and by using specific antibodies to major peanut allergens. The bioavailability of peanut proteins was analyzed using a Caco-2 epithelial cell model. The in vivo sensitizing potential of laccase-treated peanut proteins was analyzed using a mouse model of food allergy. Finally, peanut polyphenols were analyzed by UHPLC-MS/MS, before and after the enzymatic reaction with laccase. Laccase treatment of peanut proteins yielded a covalently cross-linked material, with the modified tertiary structure of peanut proteins, improved bioavailability of Ara h 2 (by 70 fold, p < 0.05) and modulated allergic immune response in vivo . The modulation of the immune response was related to the increased production of IgG2a antibodies 11 fold ( p < 0.05) and reduced IL-13 secretion in in vitro cultured splenocytes 7 fold ( p < 0.05). Analysis of the peanut polyphenol content and profile by HPLC-MS/MS revealed that laccase treatment depleted the peanut extract of polyphenol compounds leaving mostly isorhamnetin derivatives and procyanidin dimer B-type in detectable amounts. Treatment of complex food extracts rich in polyphenols with laccase results in both protein cross-linking and modification of polyphenol compounds. These extensively cross-linked proteins have unchanged potency to induce allergic sensitization in vivo, but certain immunomodulatory changes were observed.